Politicizing Social Inequality: Competing Narratives From the Alternative for Germany and Left-Wing Movement Stand Up - Schmidtke, Oliver (Frontiers in Sociology, 2020)
This article investigates the link between rising levels of social inequality and years of austerity on the one hand and the rise of populist, anti-establishment protest on the other. This connection is explored by analyzing the discursive practices of activists as a way of reconstructing the key argumentative and emotional structures organizing actors' understanding of politics. Empirically the article is based on 40 narrative interviews with supporters of the German right-wing, anti-immigrant party, Alternative for Germany (AfD), and the newly established left-wing movement Stand Up. The findings of the discursive analysis point to a profound sense of exclusion amongst left- and right-wing populist affiliates defined both in socio-economic terms and with a view to being deprived of a proper political voice. At the same time, the results show that the supporters of the AfD, in contrast to those from Stand Up, develop a strong, mobilizing collective identity that is instrumental in popularizing their discontent with the political establishment: The dramatized conflict between the virtuous German people and the threatening Other—manifested primarily by immigrants and the European Union—provides an emotionally charged binary that is at the core of the contemporary populist resurgence across Western democracies. In addition, the collective identity is instrumental in offering a particular interpretation of the origins of and desirable response to growing inequality that rely more on culturalist rather than traditional class-based arguments. Building on this analysis, the article offers an interpretation of the relative weakness of the populist left that, in the German context, so far has not succeeded in using deepening socio-economic cleavages for their political mobilization effectively.